Pengaruh Sistem Pengolahan Tanah dan Penggunaan Mulsa Terhadap Populasi Mikroorganisme dan Unsur Hara Pada Daerah Rhizosfer Tanaman Kedelai (Glycine Max L.) - PERMANA, IDA BAGUS PUTU WAHYU; ATMAJA, I WAYAN DANA; NARKA, I WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.1, Januari 2017, 2017)
The Effect of Tillage System and Mulch Use for The Population of Microorganisms and Nutrients in The Soybean (Glycine max L.) Rhizosphere Area This study aims to determine the effect of tillage systems and mulching to microorganisms population change and nutrients in the rhizosphere area of the soybean crop. This study began in January 2014 until April 2014. Soil sampling conducted in Sedap Malam Street South Denpasar, while the analysis was conducted in the Laboratory of Soil Science Udayana University, Phytopathology Laboratory and Analytical Laboratories Udayana University. The study design was Randomized Block Design where the first factor is the Soil Treatment System Conventional processing system and no-tillage, while the second factor is the use of rice straw mulch, plastic mulch, and without mulch. Each treatment was repeated 5 times.Cultivation systems and the use of mulch, affect the population of bacteria in the rhizosphere of soybean plants. TP namely (24.4 x 107 cfu g-1), followed by treatment with KT (23.4 x 107 cfu g-1), TJ (18.6 x 107 cfu g-1), KJ (15.9 x 107 cfu g-1) , TT (9.4 x 107 cfu g-1) and the lowest is the KP (9 x 107 cfu g-1) .The system tillage and the use of mulch, affect the population of fungus in the rhizosphere of soybean plants. Total bacteria highest TP (25.8 x 107 cfu g-1), KT (24.8 x 107 cfu g-1), TJ (19.2 x 107 cfu g-1), KJ (17.2 x 107 cfu g-1), TT (10.8 x 107 cfu g-1) and the lowest is the KP (10.4 x 107 cfu g-1) .The system tillage and mulching affect the content of macro nutrients in the rhizosphere of plants soy. Highest nutrient C TT (14.67) and the lowest KJ (5.19). The highest N elements TJ (0.27) KT lowest (0.12). The highest P nutrients (114.72) KP lows (75.76). K highest nutrient TT (2721.7) and the lowest KP (1085.04). The highest Ca nutrients in TJ (8930.78) and the lowest KJ (3034.85). The highest nutrient S TP (0.0495) and the lowest TJ (0.0257). And nutrient highest Mg TJ (1566.82) and KP (529.12) .The system tillage and mulching different effect on the nutrient content of N, P and K on soybean plant tissue that showed significantly different interactions between each each factor. The highest nutrient N in KP (1.88) and the lowest in the TT (1.35). The highest P nutrients in TJ (288.97) and the lowest in the TT (211.78). The highest nutrient in KP (5479.81) and the lowest in the TJ (3565.56).
Keywords: Tillage System; Mulch; and Soybeans